Extreme seascape drives local recruitment and genetic divergence in brooding and spawning corals in remote north‐west Australia. (22nd June 2020) - Underwood, Jim N.; Richards, Zoe; Berry, Oliver; Oades, Daniel; Howard, Azton; Gilmour, James P.
Abstract: Management strategies designed to conserve coral reefs threatened by climate change need to incorporate knowledge of the spatial distribution of inter‐ and intra‐specific genetic diversity. We characterized patterns of genetic diversity and connectivity using single nucleotide polymorphisms (SNPs) in two reef‐building corals to explore the eco‐evolutionary processes that sustain populations in north‐west Australia. Our sampling focused on the unique reefs of the Kimberley; we collected the broadcast spawning coral Acropora aspera ( n = 534) and the brooding coral Isopora brueggemanni ( n = 612) across inter‐archipelago (tens to hundreds of kilometres), inter‐reef (kilometres to tens of kilometres) and within‐reef (tens of metres to a few kilometres) scales. Initial analysis of A. aspera identified four highly divergent lineages that were co‐occurring but morphologically similar. Subsequent population analyses focused on the most abundant and widespread lineage, Acropora asp‐c. Although the overall level of geographic subdivision was greater in the brooder than in the spawner, fundamental similarities in patterns of genetic structure were evident. Most notably, limits to gene flow were observed at scales <35 kilometres. Further, we observed four discrete clusters and a semi‐permeable barrier to dispersal that were geographically consistent between species. Finally, sites experiencing bigger tides were more connected to the metapopulation and had greater gene diversity than those experiencing smaller tides. Our data indicate that the inshore reefs of the Kimberley are genetically isolated from neighbouring oceanic bioregions, but occasional dispersal between inshore archipelagos is important for the redistribution of evolutionarily important genetic diversity. Additionally, these results suggest that networks of marine reserves that effectively protect reefs from local pressures should be spaced within a few tens of kilometres to conserve the existing patterns of demographic and genetic connectivity.